The Preparedness of Student Teachers in Open and Distance Learning Environments for the Classroom - E. C. Du Plessis (MDPI AG, 2023)
Teaching practice is crucial to preparing teachers for teacher education globally. Studies on open and distance learning (ODL) environments, in which collaboration and discussion play a crucial role, ought to inform the design of distance learning. They should also force a more in-depth examination of and interest in teaching practice in higher education. Learning is seen as a positive experience, whether entirely lecturer-room-based or distance-based. It is essential to combine theory and practice with efficient distance training as part of work-integrated learning. Consequently, this study aimed to determine the perceived classroom skills of ODL student teachers during the teaching practice sections associated with their Postgraduate Certificate in Education (PGCE) course. The objective of ascertaining the preparedness of ODL student teachers after their PGCE program carries substantial importance in guaranteeing the quality, efficiency, and influence of the education system by cultivating competent and well-equipped teachers. A qualitative research approach was used to gather, analyse, and interpret data. Fifteen (15) student teachers registered at a College of Education of an ODL organisation were invited to participate in the research voluntarily. In the light of the research findings, it is suggested that extra care be given to the collaboration between academic lecturers, mentor teachers and student teachers, as well as to the expectations and duties of these role-players.